La Gestión del Conocimiento en las Empresas, su importancia y dependencia del Estilo del Liderazgo de la Alta Gerencia - Guerrero Bejarano, María Auxiliadora (2016)
This study examines the importance of knowledge management within companies and how it can be influenced by leaders. The concept of business process contains knowledge, product development and all aspects that are part of Business Know How, therein lies the importance of good governance and development.